GROUNDWATER QUALITY AND OBSERVATION WELLS - Mladen Zelenika (Rudarsko-geološko-naftni Zbornik, 1997)
Groundwater in the aquifers in river valleys is the mot important resource for supply of drinking water in many regions. There are intensive human activities, such as construction and operation hydroelectric power and industrial plants, forest clearance, irrigation and cropping of land, water supply and sanitation works, and particularly the accidental pollution in one town or country can reduce water availability to itself, and to another (downstream) town or country. Observation wells are not commonly used for sampling of groundwater, but in many instances it may still be the only way to collect sample of groundwater. This paper deals with the construction of observation wells installed and developed in confined or unconfined aquifer to observe and monitor time depending data, such as water level, groundwater quality and indications of contaminant transport in groundwater flow.